Analysis of Vocational High School Students’ Critical Thinking Skills in Clean Water Management in Banyuasin - Marlina, Leni; Maharani, Melinda; Sriyanti, Ida (Proceeding of International Joint Conference on UNESA, 2025)
This study aims to analyze the critical thinking skills of vocational high school (SMK) students in Banyuasin Regency in the context of clean water management through the topic “substances and their changes” in the Science and Social Studies (IPAS) subject. A descriptive quantitative approach was employed, involving 196 students selected using purposive sampling from seven SMK schools. Data were collected through a critical thinking test based on five indicators : (1) basic clarification; (2) basis for decision; (3) inference; (4) advanced clarification; and (5) assumptions and integration complemented by semi-structured interviews with 22 IPAS teachers. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The results showed an average student score of 50.67, indicating a moderate level of critical thinking, with the highest achievement in decision-making (63%) and the lowest in inference (30%). Sub-indicator analysis revealed strengths in asking clarification questions (70%) and weaknesses in making and evaluating value judgments (22%). Teacher interviews revealed that students showed high enthusiasm and creativity when dealing with real-life issues but struggled with deep scientific understanding. The novelty of this study lies in its analysis of SMK students’ critical thinking in addressing local environmental issues, particularly clean water management. The findings suggest the importance of integrating local relevance with STEM-based instructional media to enhance students’ critical thinking skills.